Principles of Fertilization and Irrigation Management for Vegetables Crops Grown in Florida in the BMP Era: Introduction - Eric Simonne; George Hochmuth (EDIS)
Adequate management of fertilization and irrigation has always been recognized as one of the keys to successful vegetable production in Florida. Thus, fertilization and irrigation practices have aimed at supplying enough nutrients and water to ensure economical yields. This document is HS897, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2003.